2009
DOI: 10.1007/s11547-009-0449-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tadalafil on prostate haemodynamics: preliminary evaluation with contrast-enhanced US

Abstract: In patients with BPH, vascular changes are observed in the prostate after Tadalafil administration, which can be detected with CEUS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 25 publications
0
29
0
1
Order By: Relevance
“…[10][11][12] PDE5 inhibitors acts by upregulation of the NO/cGMP activity. Preclinical studies reported partial reversal of nor-epinephrine-and endothelin-1-reduced prostatic tissue contraction 13 and an anti-proliferative effect on cultured prostate and bladder smooth muscle cells 14 . These mechanisms may decrease smooth muscle tension in the prostatic stroma and capsule and attenuate cellular proliferation associated with prostate/bladder hypertrophy respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] PDE5 inhibitors acts by upregulation of the NO/cGMP activity. Preclinical studies reported partial reversal of nor-epinephrine-and endothelin-1-reduced prostatic tissue contraction 13 and an anti-proliferative effect on cultured prostate and bladder smooth muscle cells 14 . These mechanisms may decrease smooth muscle tension in the prostatic stroma and capsule and attenuate cellular proliferation associated with prostate/bladder hypertrophy respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As a result there is decrease in smooth muscle tension in the prostatic stroma and capsule and also attenuate cellular proliferation associated with prostate/bladder neck hypertrophy respectively. Tadalafil had shown improved blood flow to prostate on color doppler ultrasound 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that PDE5 inhibitors can improve lower urinary tract symptoms (LUTS) and urodynamic parameters [3,4,5]. These indications may be sufficient to convince physicians to prescribe PDE5 inhibitors once daily to patients with erectile dysfunction (ED) with or without concomitant LUTS.…”
Section: Introductionmentioning
confidence: 99%